PENINGKATAN KREATIVITAS SISWA SDN 1 KAMARANG MELALUI MODEL PROJECT BASED LERNING DI KURIKULUM MERDEKA - Dian Dwi Agustin; Widia Nur Jannah; Aiman Faiz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The Project Based Learning model can improve student learning outcomes, as well as improve students' creative thinking skills and retention, and students' understanding of mathematical concepts. This research is classroom action research (PTK), the research process is in accordance with classroom action research procedures carried out in a cycle process. Each cycle consists of planning, action, observation and reflection. Based on cycle 1 and cycle 2 carried out by researchers.